2008
DOI: 10.1002/oa.998
|View full text |Cite
|
Sign up to set email alerts
|

Bone weight: new reference values based on a modern Portuguese identified skeletal collection

Abstract: Skeletal weight and/or weight of the different bones of the human skeleton are currently used in a wide range of applications such as archaeological cremations and forensics. Still, few reference values are available that compare the mean weights for the different skeletal parts. In this paper we present new reference values for total skeletal weight, including the weight of the different skeletal bones based on a modern Portuguese Identified Skeletal Collection (CEI) curated in the Museum of Anthropology of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…In our recent analyses of population-based data of 9424 primary bone tumours from England diagnosed during the period 1979 to 2003, we show that Ewing sarcomas of the central axis (vertebral column, ribs, sternum, clavicle, pelvic bones, sacrum and coccyx) and long bones of the lower limb have nearly equal incidence peaks (Arora et al, in preparation). This pattern broadly co-relates with the structure of the adult human skeleton, which at 29 to 39 years of age, is made up of bones of the central axis (29%), long bones of the lower limb (25%), skull and facial bones (21%), long bones of the upper limb (15%), and short bones of the upper and lower limbs (9%) [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent analyses of population-based data of 9424 primary bone tumours from England diagnosed during the period 1979 to 2003, we show that Ewing sarcomas of the central axis (vertebral column, ribs, sternum, clavicle, pelvic bones, sacrum and coccyx) and long bones of the lower limb have nearly equal incidence peaks (Arora et al, in preparation). This pattern broadly co-relates with the structure of the adult human skeleton, which at 29 to 39 years of age, is made up of bones of the central axis (29%), long bones of the lower limb (25%), skull and facial bones (21%), long bones of the upper limb (15%), and short bones of the upper and lower limbs (9%) [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies are under-powered, lack comprehensive data and show inconsistencies. Methods Relevant studies linking osteosarcoma and Ewing sarcoma with height at diagnosis were identified in two major online databases, Medline (1950to 2009) and Embase (1980to 2009. Outcomes in individual studies were reported as standard deviation (SD) scores or percentages of study population with height at diagnosis above the median of the reference population.…”
mentioning
confidence: 99%
“…To infer more detail regarding the thoroughness of the retrieval of human bones in this pit, bone representation of adult individuals was checked for possible irregularities using bone weight of the different parts of the skeletons (for more details about this method see Silva et al, 2009). This approach is particularly helpful in samples where the bones are reduced to tiny pieces including a great percentage of fragments without complete identification.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the representation of body parts and confirm the presence of each anatomical region or determine whether or not certain body parts had been selected, a comparison with other samples was performed. Figure 17.5 shows the comparison between the percentage weight of each anatomical category of the Apuan adult sample, with the values indicated by Silva et al (2009) based on a modern (not burned) Portuguese Identified Skeletal Collection (PISC, representing the bone distribution in normal skeletons) and with the cremated remains from the Villanovian necropolis of Pisa (representing the bone distribution in cremains). The Apuans show very similar frequencies with Pisa for every skeletal region and with the PISC sample only for the frequencies of the skull and the lower limbs.…”
Section: Quantitative Analysismentioning
confidence: 99%